The effect of a psychological training program on the emotional regulation of the tactical and offensive intelligence of the fencing players (Journal of the College of Basic Education, 2023)
Summary of the research:The study aimed to prepare a psychological training program according to the emotional regulation and the effect of this approach on the tactical and offensive intelligence of the fencing players. Diyala) for the fencing of 16 players for the category of applicants, the researcher used (4) of them in the reconnaissance experiment, and the rest of the players were selected as a sample for the research, and thus the number of the sample became (12) players, with a percentage of (75%) of the original community, so the researcher divided the sample into two groups randomly by lottery, the first represents the experimental group and the second represents the control group, each group consists of (6) players. Results The researcher concluded that the psychological training program proved that the emotional regulation contributes to improving the tactical intelligence of the players. To prepare the players psychologically, similar to the physical and skillful coach, for the success of the training process.Offensive for fencing players